THE IMPACT OF SYNTAX MASTERY ON STUDENTS’ WRITING ACCURACY - Aisyah Amru; Nadia Wulandari; Nasywa Sakinah; Izzati Amirah Sari; Siti Ismahani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study investigates the effect of students’ syntax mastery on writing accuracy in English as a Foreign Language (EFL). Writing accuracy is closely related to the correct application of syntactic rules, including sentence structure, word order, and grammatical relationships. An experimental research design was employed involving ten first-semester EFL students. Data were collected through a syntax mastery test and a writing task designed to measure students’ accuracy in constructing grammatical sentences. Pre-test and post-test scores were analyzed to examine the relationship between syntax mastery and writing performance. The results indicate that students with higher levels of syntax mastery achieved significantly better writing accuracy compared to those with lower mastery. These students demonstrated greater ability to produce grammatically correct and well-structured sentences. The findings underscore the importance of syntax instruction in enhancing EFL learners’ writing accuracy. Consequently, the integration of syntax-focused teaching strategies is recommended to support the development of accurate writing skills in EFL classroom contexts. ABSTRAK Penelitian ini menyelidiki pengaruh penguasaan sintaksis siswa terhadap akurasi menulis dalam konteks Bahasa Inggris sebagai Bahasa Asing (EFL). Akurasi menulis sangat berkaitan dengan penerapan aturan sintaksis yang benar, termasuk struktur kalimat, urutan kata, dan hubungan gramatikal. Desain penelitian eksperimen digunakan dengan melibatkan sepuluh mahasiswa EFL semester pertama. Data dikumpulkan melalui tes penguasaan sintaksis dan tugas menulis yang dirancang untuk mengukur akurasi siswa dalam membangun kalimat yang gramatikal. Skor pre-test dan post-test dianalisis untuk mengkaji hubungan antara penguasaan sintaksis dan performa menulis. Hasil penelitian menunjukkan bahwa siswa dengan tingkat penguasaan sintaksis yang lebih tinggi memperoleh akurasi menulis yang secara signifikan lebih baik dibandingkan siswa dengan penguasaan rendah. Siswa tersebut menunjukkan kemampuan lebih besar dalam menghasilkan kalimat yang gramatikal dan tersusun dengan baik. Temuan ini menegaskan pentingnya pembelajaran sintaksis dalam meningkatkan akurasi menulis siswa EFL. Oleh karena itu, integrasi strategi pengajaran yang berfokus pada sintaksis direkomendasikan untuk mendukung pengembangan keterampilan menulis yang akurat dalam konteks kelas EFL.